2017
DOI: 10.1155/2017/2794040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Pollination on the Expression of Dangshan Su Pear MicroRNA

Abstract: The high-throughput sequencing of pear “Dangshan Su” × “Yali” (whose fruits lignin and stone cell content are high and quality is poor) and pear “Dangshan Su” × “Wonhwang” (whose fruits with low content of lignin and stone cell and the quality are better ) found that the expressions of these two miRNAs (pyr-1809 and pyr-novel-miR-144-3p) were significantly different; their corresponding target genes encode two kinds of laccase (Pbr018935.1 and Pbr003857.1). qRT-PCR results showed that these two enzymes are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Genomic comparisons are a comparatively quick and active way to transfer genomic knowledge acquired in one taxon to another ( Lyons et al, 2008 ). In this study, synteny analysis was carried out using MCScanX software and whole genome sequences to visualize the locations of homologous or orthologous genes ( Cao et al, 2016 ; Cheng et al, 2017 ). The identification of orthologous GhZHD genes will further define the evolutionary history of this gene family.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic comparisons are a comparatively quick and active way to transfer genomic knowledge acquired in one taxon to another ( Lyons et al, 2008 ). In this study, synteny analysis was carried out using MCScanX software and whole genome sequences to visualize the locations of homologous or orthologous genes ( Cao et al, 2016 ; Cheng et al, 2017 ). The identification of orthologous GhZHD genes will further define the evolutionary history of this gene family.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a PPR protein (pyrus_GLEAN_10024043) was involved in plant development and RNA metabolism [ 56 ]. Given that miRNA could affect lignin metabolism and stone cell development via the regulation of laccases, this result suggests that the PPR protein may interact with RNA to control stone cell development [ 2 , 57 ]. PP2C25 (CUFF51.591.1) and NUDTs (pyrus_GLEAN_10031740 and pyrus_GLEAN_10035206) play roles in phosphorus modification and the hydrolysis of phosphorus-containing substances, respectively [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This feature is a key factor in the high stone cell content of the CD fruit. PbSAD expression in CD fruit was significantly reduced compared with CL fruit, suggesting that the G/S ratio of CD fruit was increased compared with CL fruit, resulting in lignin stability and difficulties in degrading and forming highly aggregated SCCs [ 2 , 13 ]. 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the content and size of stone cells are not only determined by the genotype of pear varieties, but also by the external environment and cultivation methods, such as pollination, water, bagging, and exogenous mineral elements [7,[21][22][23][24]. Pears are gametophytic self-incompatible plants and they cannot be inseminated by self-pollination [2].…”
Section: Introductionmentioning
confidence: 99%